Identification of a lipopolysaccharide alpha-2,3-sialyltransferase from Haemophilus influenzae. - Hood, D; Cox, A; Gilbert, M; Makepeace, K; Walsh, S; Deadman, M; Cody, A; Martin, A; Månsson, M; Schweda, E; Brisson, JR; Richards, J; et al. (2001)
We have identified a gene for the addition of N-acetylneuraminic acid (Neu5Ac) in an alpha-2,3-linkage to a lactosyl acceptor moiety of the lipopolysaccharide (LPS) of the human pathogen Haemophilus influenzae. The gene is one that was identified previously as a phase-variable gene known as lic3A. Extracts of H. influenzae, as well as recombinant Escherichia coli strains producing Lic3A, demonstrate sialyltransferase activity in assays using synthetic fluorescent acceptors with a terminal galactosyl, lactosyl or N-acetyl-lactosaminyl moiety. In the RM118 strain of H. influenzae, Lic3A activity is modulated by the action of another phase-variable glycosyltransferase, LgtC, which competes for the same lactosyl acceptor moiety. Structural analysis of LPS from a RM118:lgtC mutant and the non-typeable strain 486 using mass spectrometry and nuclear magnetic resonance (NMR) spectroscopy confirmed that the major sialylated species has a sialyl-alpha-(2-3)-lactosyl extension off the distal heptose. This sialylated glycoform was absent in strains containing a lic3A gene disruption. Low amounts of sialylated higher molecular mass glycoforms were present in RM118:lgtC lic3A, indicating the presence of a second sialyltransferase. Lic3A mutants of H. influenzae strains show reduced resistance to the killing effects of normal human serum. Lic3A, encoding an alpha-2,3-sialyltransferase activity, is the first reported phase-variable sialyltransferase gene.